Annealing temperature effects on (111)-oriented BiFeO3 thin films deposited on Pt/Ti/SiO2/Si by chemical solution deposition. Issue 41 (22nd September 2015) - Jin, Linghua; Tang, Xianwu; Song, Dongpo; Wei, Renhuai; Yang, Jie; Dai, Jianming; Song, Wenhai; Zhu, Xuebin; Sun, Yuping
Abstract : As the most-studied multiferroic material, (111)-oriented BiFeO3 (BFO) thin films are desirable due to the highest polarization in the (111) plane. Abstract : As the most-studied multiferroic material, (111)-oriented BiFeO3 (BFO) thin films are desirable due to the highest polarization in the (111) plane. The difficulty of achieving large-area (111)-oriented BFO films on silicon wafers towards implementation with silicon technology has hindered the development of BFO films. Herein, we report the annealing temperature effects on chemical solution deposition (CSD) derived BFO films on Pt(111)/Ti/SiO2 /Si substrates without any buffer layer. The derived BFO films shows a strong (111) orientation with a distorted rhombohedral structure and R 3 c space group. The annealing temperature effects on the microstructures as well as the properties were investigated. A dense and crack-free surface was obtained in the low-temperature annealed films. Relatively high room-temperature remnant polarization 2 P r (120–140 μC cm −2 ) could be obtained with low leakage (∼10 −5 A cm −2 at 200 kV cm −1 ). Scanning electron microscopy and transmission electron microscopy showed that this is an available route for fabricating large-area (111)-oriented BFO films on silicon-based wafers with high 2 P r using low-cost solution processing.